MOF material for shaping, shaped body, gas adsorbent, gas adsorption device, and method for producing MOF material for shaping
By localizing silicon on the surface of MOF crystal particles to enable silicon-mediated bonding, the MOF material avoids the pore-blocking issues associated with binder use, maintaining high gas adsorption performance and reducing binder requirements.
Patent Information
- Application Number
- JP2023144561
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Conventional methods for shaping MOF materials using binders block the pores of MOF, reducing its specific surface area and impairing gas adsorption and separation functions, while also decreasing the adsorption capacity per unit weight due to the addition of binders.
A morphological MOF material is developed where silicon (Si) is localized on the surface of the crystal particles, facilitating silicon-mediated bonding to eliminate the need for binders or reduce their amount, thereby preserving the MOF's performance.
The MOF material maintains its gas adsorption performance without the use of binders, as evidenced by carbon dioxide adsorption isotherms showing 1.5 times the adsorption amount of binder-free MOF materials at specific pressures and temperatures.
Smart Images

Figure 2025037569000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a MOF material for shaping, a shaped body, a gas adsorbent, a gas adsorption device, and a method for producing a MOF material for shaping. [Background technology]
[0002] MOFs (Metal Organic Frameworks) are complex crystals formed by the coordination of metal ions and organic ligands. They have a highly regular porous coordination network structure formed by metal ions and organic ligands, and have numerous nanospaces inside. By utilizing such nanospaces, MOFs can be used as materials for occluding and separating various substances such as gases, and as catalyst materials. Since MOFs are generally synthesized as powders, when they are used as materials for occluding and separating gases or as catalyst materials as described above, it is necessary to mold (shape) the powdered MOFs. As a method for shaping powdered MOFs, a molding method using a binder such as a binder or a polymer has been known (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4980918 [Patent Document 2] Patent No. 6272696 Summary of the Invention [Problem to be solved by the invention]
[0004] However, when MOFs are shaped by binding MOF particles using binders or the like as described above, the pores of the porous MOF are blocked, reducing the specific surface area of the MOF, which may result in a loss of the function of absorbing and separating gases using the nanospace. Even if the function of the MOF is not reduced, there is a problem that the amount of adsorption per unit weight is reduced by the amount of binder added. Therefore, there has been a demand for a technology to shape MOFs without using a binder or other binding agent while suppressing the deterioration of MOF performance, or by reducing the amount of binder or other binding agent used. [Means for solving the problem]
[0005] The present disclosure can be realized in the following forms. (1) According to one embodiment of the present disclosure, there is provided a metal-organic framework (MOF) material for shaping, which contains silicon (Si) localized on the surface of crystal particles constituting the MOF. With this form of MOF material for shaping, bonds are formed via silicon on the surface of the MOF, making it possible to eliminate the need for a binding agent such as a binder to shape the MOF, or to reduce the amount of binding agent such as a binder used. (2) In the MOF material for shaping, the atomic fraction ratio of the complex metal contained in the MOF to silicon (Si) (complex metal contained in the MOF:Si) may be 0.98:0.02 to 0.9:0.10. With this configuration, it is possible to obtain the effect of facilitating shaping of the MOF while suppressing a decrease in the performance of the MOF, such as the gas adsorption amount, caused by an excessive amount of Si added. (3) According to another aspect of the present disclosure, there is provided a shaped object made of the MOF material for shaping described in (1). With this form of shaped body, bonds are formed via silicon on the surface of the MOF, making it unnecessary to use a binding agent such as a binder to shape the MOF, or making it possible to reduce the amount of binding agent such as a binder used. (4) The shaped body may have an average particle size of 1 mm or more. This configuration enhances the effects of forming MOFs, such as making the MOF material easier to handle, reducing pressure loss in an apparatus that includes the MOF material, and reducing problems that may occur during evacuation for gas separation when the MOF material is used in a gas adsorption apparatus. (5) In the MOF material for shaping in the above-mentioned form, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C. and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount may be 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. With such a configuration, the carbon dioxide adsorption performance of the MOF material for shaping can be ensured. (6) In the MOF material for shaping in the above-mentioned form, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C. and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount may be 1.5 times or more the carbon dioxide adsorption amount of an MOF having a composition common to the MOF material for shaping except that it does not contain silicon. With such a configuration, the carbon dioxide adsorption performance of the MOF material for shaping can be ensured. (7) In the above-mentioned shaped body, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C. and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount may be 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the above-mentioned MOF material for shaping except that it does not contain silicon. With such a configuration, the carbon dioxide adsorption performance of the shaped body can be ensured. (8) In the above-mentioned shaped body, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C. and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount may be 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the above-mentioned MOF material for shaping except that it does not contain silicon. With such a configuration, the carbon dioxide adsorption performance of the shaped body can be ensured. (9) In the MOF material for molding having the above-mentioned form, when the carbon dioxide adsorption / desorption isotherm was measured at a measurement temperature of 0°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 45 cm 3 (STP) / g) or more. With this configuration, the carbon dioxide adsorption performance of the MOF material for shape transfer can be ensured. (10) In the MOF material for molding having the above-mentioned form, when the carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 is 25 cm 3 (STP) / g) or more. With this configuration, the carbon dioxide adsorption performance of the MOF material for shape transfer can be ensured. (11) In the above-mentioned shaped body, when the carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 is 40 cm 3 (STP) / g) or more. With this configuration, the carbon dioxide adsorption performance of the shaped object can be ensured. (12) In the above-mentioned shaped body, when the carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 is 20 cm 3 (STP) / g) or more. With this configuration, the carbon dioxide adsorption performance of the shaped object can be ensured. (13) According to yet another aspect of the present disclosure, there is provided a gas adsorbent for adsorbing and releasing a gas, the gas adsorbent being constituted by the shaped body according to any one of (3), (4), (7), (8), (11), and (12). In this form of gas adsorbent, silicon-mediated bonds are formed on the surface of the MOF, making it possible to eliminate the need for a binding agent such as a binder when shaping the MOF to produce a gas adsorbent, or to reduce the amount of binding agent such as a binder used. (14) According to yet another aspect of the present disclosure, there is provided a gas adsorption device including the gas adsorbent according to (13). According to the gas adsorption device of this embodiment, it is possible to suppress problems that occur in association with evacuation for gas separation. (15) According to yet another aspect of the present disclosure, there is provided a method for producing an MOF material for shaping, comprising adding to a metal-organic framework (MOF) a silane derivative having a functional group capable of forming a chemical bond with a functional group on the surface of the MOF. According to this method for producing a MOF material for shaping, the silane derivative forms a chemical bond with the functional group on the surface of the MOF, and the MOF and the silane derivative are bound together, making it easier to shape the MOF. As a result, it becomes unnecessary to use a binder or other binding agent to shape the MOF, or it becomes possible to reduce the amount of the binder or other binding agent used. The present disclosure can be realized in various forms other than those described above, for example, in the form of a gas adsorbent constituted by a shaped body, a gas adsorption device including a gas adsorbent, a method for manufacturing a shaped body, etc. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is an explanatory diagram showing the structure of UiO-66-COOH into which a carboxy group has been introduced. [Diagram 2] FIG. 2 is an explanatory diagram showing an example of a silane derivative. [Diagram 3] FIG. 1 is an explanatory diagram showing a schematic configuration of the MOF material for shaping according to the present embodiment. [Figure 4] An explanatory diagram showing the prepared MOF material for shaping and the shaped body. [Figure 5A] TEM image of Zr elemental mapping performed on sample S2. [Figure 5B] TEM image of sample S2 when Si element mapping was performed. [Figure 6A] TEM image of Zr elemental mapping performed on sample S11. [Figure 6B] TEM image of sample S11 when Si element mapping was performed. [Figure 7]FIG. 11 is an explanatory diagram showing the results of determining atomic fractions for samples S1 to S3 and S11. [Figure 8] FIG. 13 is an explanatory diagram showing a graph in which calculation results of atomic fractions are plotted. [Figure 9] FIG. 2 is an explanatory diagram showing the results of measuring a carbon dioxide adsorption / desorption isotherm at 25° C. [Figure 10] FIG. 2 is an explanatory diagram showing the measurement results of the BET specific surface area and the amount of carbon dioxide adsorption at 0° C. [Figure 11] FIG. 2 is an explanatory diagram showing the results of measuring a carbon dioxide adsorption / desorption isotherm at 0° C. [Figure 12] FIG. 2 is an explanatory diagram showing the measurement results of the BET specific surface area and the amount of carbon dioxide adsorption at 25° C. [Figure 13] FIG. 2 is an explanatory diagram showing the results of measuring a carbon dioxide adsorption / desorption isotherm at 25° C. [Figure 14] FIG. 2 is an explanatory diagram showing the results of measuring a carbon dioxide adsorption / desorption isotherm at 25° C. [Figure 15] FIG. 2 is an explanatory diagram showing the results of measuring a carbon dioxide adsorption / desorption isotherm at 25° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] A. Composition of MOF material for shaping: The MOF material for excipient of this embodiment is composed of a metal-organic framework (MOF), and contains silicon (Si) localized on the surface of the crystal particles constituting the MOF. MOF is a porous metal complex obtained by utilizing the self-organization of metal ions and organic ligands, and is a crystalline material that forms a highly regular array structure, and realizes a high surface area by having countless nano spaces inside the array structure. The MOF material for excipient of this embodiment "contains silicon (Si) localized on the surface of the crystal particles constituting the MOF", and the metal ions and organic ligands constituting the MOF do not substantially contain silicon (Si). The MOF material for excipient of this embodiment contains silicon (Si) localized on the surface of the crystal particles constituting the MOF, and therefore it is possible to excipient without using a binder such as a binder, or by reducing the amount of binder such as a binder used, while suppressing the deterioration of the performance of the MOF caused by the use of a binder, etc. The MOF material for shaping according to this embodiment can be produced by preparing an MOF formed using a material that is substantially free of silicon (Si), and then adding a silane derivative, which is a compound that contains silicon (Si), to the MOF, as described below.
[0008] The MOF constituting the MOF material for shaping of the present embodiment may be appropriately selected depending on the application of the shaped body formed by the MOF material for shaping (for example, the application as gas occlusion, separation, or catalyst, the type of target gas, etc.), and is not particularly limited. The metal ion as the complex metal constituting the MOF is, for example, a zirconium ion (Zr 4+ ), zinc ion (Zn 2+ ), copper ions (Cu 2+ ), aluminum ion (Al 3+ ), iron ion (Fe 3+ ), cobalt ion (Co 3+ ), nickel ion (Ni 2+ ), magnesium ion (Mg 2+ ), chromium ion (Cr 3+ ), manganese ion (Mn 2+) can be at least one selected from the group consisting of carboxylic acids, such as dicarboxylic acids including aromatic dicarboxylic acids such as terephthalic acid, amines, imidazoles, and derivatives thereof. The combination of the complex metal and the organic ligand makes it possible to adjust the chemical stability of the MOF obtained, the pore size and the properties of the pore surface, the type and amount of gas adsorbed as a result, or various performances such as catalytic activity, magnetism, and polarity. For example, when using the MOF material for shaping by utilizing its property of adsorbing gases such as carbon dioxide, it is desirable that the MOF material for shaping has a property of suppressing the amount of adsorption of other types of gases such as nitrogen and water vapor. In addition, the MOF constituting the MOF material for shaping of this embodiment may be a MOF having a relatively rigid framework structure and exhibiting a specific pore size, or may be a so-called soft MOF having a relatively flexible framework structure in which the framework expands and contracts with the adsorption and desorption of gas.
[0009] The MOF material for shaping according to the present embodiment can be produced by adding a silane derivative to the MOF. The silane derivative added to the MOF is a silane derivative having a functional group (hereinafter also referred to as a "silane derivative side functional group") capable of forming a chemical bond together with the functional group on the surface of the MOF (hereinafter also referred to as a "MOF side functional group"). Here, the "chemical bond" formed by the silane derivative together with the MOF side functional group can include both a chemical bond formed between the silane derivative and the MOF side functional group, and a chemical bond formed between silane derivatives. Such a "chemical bond" can be a chemical bond including a bond represented by a siloxane bond (-Si-O-Si-) and (-O-Si-). Examples of the "MOF side functional group" involved in such a chemical bond include a carboxy group (-COOH) and a hydroxy group (-OH). When the organic ligand contained in the MOF originally has the above-mentioned "MOF side functional group", it is possible for such functional group to form a chemical bond with the silane derivative, but it is preferable to use a MOF in which a "MOF side functional group" has been further introduced to the organic ligand. The MOF material for excipient can be produced, for example, by stirring and mixing the MOF, the silane derivative, and an organic solvent such as ethanol under appropriate conditions such as room temperature, followed by removing the solvent by suction filtration or the like, and then drying under vacuum. After the above-mentioned drying process, a MOF material for excipient that can be easily turned into a powder is obtained.
[0010] Figure 1 is an explanatory diagram showing the structure of UiO-66-COOH, an example of a MOF with a "MOF side functional group" introduced into an organic ligand, in which a carboxy group (-COOH) has been introduced into the Zr-based MOF UiO-66 (Zr6O4(OH)4(BDC)6, where BDC = 1,4-benzenedicarboxylic acid). In this way, by actively introducing a "MOF side functional group" into the MOF, it is possible to increase the efficiency with which the "silane derivative side functional group" of the silane derivative added to the MOF forms a chemical bond together with the MOF side functional group.
[0011] As described above, the silane derivative added to MOF to produce the MOF material for shaping according to the present embodiment may have a "silane derivative side functional group" capable of forming a chemical bond together with the "MOF side functional group". For example, a silane coupling agent containing a hydrolyzable group such as an alkoxy group typified by a methoxy group (-OCH3) or an ethoxy group (-OC2H5) may be used as the "silane derivative side functional group". The silane derivative may be other than a silane coupling agent, and may have a "silane derivative side functional group" capable of forming a chemical bond together with the MOF side functional group. An example of a suitable silane derivative is a methoxy-type alkylsilane.
[0012] The silane derivative may have two or more "silane derivative side functional groups", and in such a case, one silane derivative molecule can be bonded to a plurality of "MOF side functional groups". When the silane derivative has two silane derivative side functional groups, for example, when the silane derivative has a linear structure constituted by an alkyl group or the like, it is desirable to have the silane derivative side functional groups at both ends of the linear structure. For example, such a silane derivative may be a silane derivative having bistrimethoxy at both ends. The number of carbon atoms (the number of methylene groups) of the alkyl group portion in the silane derivative may be, for example, 2 to 10.
[0013] Fig. 2 is an explanatory diagram showing an example of the above-mentioned silane derivative. In Fig. 2, 1,2-bis(trimethoxysilyl)ethane (e.g., KBM-3026 manufactured by Shin-Etsu Chemical Co., Ltd.) having two methylene groups, 1,6-bis(trimethoxysilyl)hexane (e.g., KBM-3066 manufactured by Shin-Etsu Chemical Co., Ltd.) having six methylene groups, and 1,8-bis(trimethoxysilyl)octane (e.g., KBM-3086 manufactured by Shin-Etsu Chemical Co., Ltd.) having eight methylene groups are shown as examples according to the difference in the linear alkyl group possessed by the silane derivative. When preparing the MOF material for shaping of the present embodiment, a single type of silane derivative may be used, or multiple types of silane derivatives mixed at any ratio may be used.
[0014] When manufacturing the MOF material for molding of this embodiment, the amount of silane derivative added to MOF is preferably small, so long as the effect of containing silicon (Si) localized on the surface of the crystal particles constituting the MOF can be obtained. For example, it is preferable to add 2.5 weight % (wt%) or less of the total of MOF and silane derivative, and it can be about 1.0 wt%. By reducing the amount of silane derivative added in this way, it is possible to prevent the pores of MOF from being blocked by the silane derivative, thereby preventing the performance of MOF (for example, gas adsorption ability) from decreasing.
[0015] In the MOF material for excipient of this embodiment, the atomic fraction ratio of the complex metal contained in the MOF constituting this MOF material for excipient and silicon (Si) (complex metal contained in MOF:Si) can be 0.98:0.02 to 0.9:0.10. Such an atomic fraction can be obtained using an EDS-equipped transmission electron microscope (TEM-EDS) or an EDS-equipped scanning transmission electron microscope (STEM / EDS). By combining the above-mentioned electron microscope with EDS, element mapping becomes possible, and the atomic fraction can be obtained by performing quantitative mapping (weight %). If the measured value of the ratio of Si (atomic fraction of Si) when the sum of the complex metal and silicon (Si) in the element composition ratio is 1 is 0.02 or more, it can be said that the MOF material for excipient contains an amount of Si that is sufficiently distinguishable from the background, and the effect of the present application that the shaping is facilitated by the localization of Si on the surface of the crystal particles constituting the MOF can be more fully obtained. Furthermore, if the measured atomic fraction of Si is 0.10 or less, it is possible to prevent the pores of the MOF from being blocked due to an excessive amount of Si added, which would result in a decrease in the performance of the MOF, such as the amount of gas adsorption. From the viewpoint of preventing an excessive amount of Si added, the atomic fraction of Si is more preferably 0.09 or less, and even more preferably 0.08 or less.
[0016] B. About the shaped body: The MOF material for shaping obtained in the form of, for example, powder by the above-mentioned manufacturing method may be used as a shaped body by molding (shaping). As a method for molding the MOF material for shaping, various methods such as injection molding, extrusion molding, hollow molding, compression molding, powder molding, calendar molding, and thermoforming can be adopted. As a shape of the shaped body, various shapes such as a spherical shape, a cylindrical shape, and a rectangular parallelepiped shape can be adopted. The shaped body formed from the MOF material for shaping of this embodiment can be used, for example, as a gas adsorbent equipped in a gas adsorption device. By forming the MOF material into a shaped body as described above, the handling of the MOF material becomes easy. In addition, by forming the MOF material into a shaped body, the pressure loss in the device equipped with the MOF material can be suppressed. Furthermore, for example, in a gas adsorption device (gas separation device) using the pressure swing adsorption method (PSA method), by forming the gas adsorbent into a shaped body, it is possible to suppress the malfunctions that occur accompanying the evacuation for gas separation. If the gas adsorbent is in powder form, problems may arise such as the gas adsorbent being sucked in and lost when the vacuum is drawn (dissipation by gas flow), or the vacuum pump may malfunction due to the intake of the powder.
[0017] The shaped body may have an average particle size of, for example, 1 mm or more. This can enhance the effects already described by forming the MOF material into a shaped body. From the viewpoint of obtaining the above-mentioned effects of shaping, the average particle size of the shaped body is more preferably 2 mm or more, and even more preferably 3 mm or more. In addition, from the viewpoint of ensuring gas diffusibility in a device equipped with a shaped body, the average particle size of the shaped body may be, for example, 10 mm or less, more preferably 8 mm or less, and even more preferably 6 mm or less. The average particle size of the shaped body can be measured by various methods as long as it can be measured with sufficient accuracy, and can be measured by, for example, a vernier caliper, a digital microscope, an image dimension measuring instrument, etc.
[0018] When the MOF material for shaping of this embodiment is molded to prepare a shaped body, a binder may be added during molding, or a binder may not be added. The presence or absence of a binder and the amount of binder added may be appropriately set according to the molding method for shaping and the performance required for the resulting shaped body. For example, when a shaped body is formed by compression molding, a relatively strong compressive force is applied during molding, so the effect of reducing the amount of binder added during molding is easily obtained, and binderless molding is facilitated. In addition, for example, when a shaped body is molded by extrusion molding, since the compressive force applied during molding is relatively small, it is also preferable to add a binder. When a powdered MOF is molded using the binding force of a binder, a binder in an amount exceeding 10 wt% is generally required, but when the MOF material for shaping of this embodiment is molded, even if a binder is added, the amount of binder added can be 10 wt% or less, and even a smaller amount can be added to sufficiently mold the body. The amount of binder added to the MOF material for shaping of this embodiment can be, for example, 2 to 5 wt %.
[0019] When a binder is used to mold the MOF material for molding of this embodiment, various binders conventionally known as binders for molding powdery materials can be used as the binder. From the viewpoint of ensuring heat resistance, it is desirable to use inorganic binders such as polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), and polyethylene oxide (PEO). Among resins that can be used as binders, PVP has higher heat resistance and is desirable because it is easy to ensure stability even under relatively high temperature conditions such as the activation treatment of MOF. Furthermore, as described above, among resins that can be used as binders, PVP exhibits a higher moisture absorption rate, making it possible to mitigate the effect of moisture on MOF. In addition, since PVP has relatively good adhesiveness and dispersibility, it becomes easier to increase the binding between MOF and silane derivative.
[0020] The shaped body obtained by molding the MOF material for shaping of the present embodiment can be applied to various devices by utilizing the properties of the MOF related to gas adsorption / separation and catalytic activity. For example, it can be a gas adsorption device equipped with a gas adsorbent constituted by the shaped body of the present embodiment. As the gas adsorption device, for example, a device using a pressure swing adsorption method (PSA) in which the pressure of the gas in an adsorption tower equipped with a gas adsorbent is changed between a predetermined high pressure state and a predetermined low pressure state, and the gas is separated by utilizing the difference between the gas adsorption amount at a high pressure during gas adsorption and the gas adsorption amount at a low pressure during gas desorption, can be mentioned. In addition, it may be a device using a temperature swing adsorption method (TSA) in which the temperature of the adsorption tower is changed between a predetermined high temperature state and a predetermined low temperature state, and the gas is separated by utilizing the difference between the gas adsorption amount at a low temperature during gas adsorption and the gas adsorption amount at a high temperature during gas desorption. Alternatively, a device using Pressure and Thermal Swing Adsorption (PTSA), which combines the above-mentioned pressure fluctuation and temperature fluctuation, may be used. The PSA method is preferable because it allows switching between the adsorption and desorption steps in a relatively short time.
[0021] The MOF material for shaping according to the present embodiment, configured as described above, is prepared by adding a silane derivative having a silane derivative side functional group capable of forming a chemical bond together with the MOF side functional group to the MOF, and has a configuration in which silicon (Si) is localized on the surface of the crystal particles constituting the MOF. Therefore, it is not necessary to use a binder or other binding agent to shape the MOF, or it is possible to reduce the amount of the binder or other binding agent used.
[0022] FIG. 3 is an explanatory diagram showing the configuration of the MOF material for shaping according to the present embodiment, which is prepared by adding a silane derivative to MOF, that is, the state in which MOF is bonded to a silane derivative to form a MOF material for shaping. When a silane derivative is added to MOF to prepare a MOF material for shaping, a hydrolyzable group of the silane derivative (e.g., a methoxy group (-OCH3)) generates a silanol (Si-OH) and an alcohol by hydrolysis, and then a condensation reaction proceeds between the silanol generated by hydrolysis and the functional group on the MOF side to form a chemical bond, and the MOF and the silane derivative are bonded together. In addition, in some silane derivatives, a condensation reaction proceeds between the silanols of the silane derivatives, and the silane derivatives are bonded together. As a result, it is considered that a MOF material for shaping as shown in FIG. 3 can be obtained. Furthermore, it is considered that some crystal particles of MOF are bonded together via the silane derivative.
[0023] In this way, the MOF side functional groups present on the surface of the MOF are bonded to each other via the silane derivative, and the shape is fixed, which is considered to facilitate the shaping of the MOF as a MOF material for shaping. In addition, it is generally difficult for a silane derivative with a relatively large molecule, such as the silane derivative having a long chain linked with a methylene group shown in Figure 2, to enter the pores of the MOF, and the bonding between the MOF side functional group and the silane derivative side functional group proceeds almost exclusively on the MOF surface. In addition, among the silane derivatives added to the MOF during the preparation of the MOF material for shaping, the excess silane derivative that was not used for bonding with the MOF surface is considered to be removed together with the solvent when the solvent is removed from the MOF in the manufacturing process of the MOF material for shaping. As a result, the silane derivative (and silicon derived from the silane derivative) is localized on the surface of the MOF. Therefore, the silane derivative is prevented from blocking the pores inside the MOF, and the deterioration of the performance of the MOF caused by the blocking of the pores of the MOF is suppressed. In particular, in the MOF material for shaping of this embodiment, the amount of silane derivative added can be made small compared to the amount of a typical binder added, thereby enhancing the effect of suppressing the blocking of pores due to the addition of the silane derivative.
[0024] In addition, the MOF material for shaping according to the present embodiment and the shaped body formed from such a MOF material for shaping can increase the amount of gas adsorption compared to the MOF constituting the MOF material for shaping. This is believed to be because, as shown in Fig. 3, the MOF and the silane derivative are bonded to each other on the surface of the MOF, new sites are formed between the surface of the MOF and the silane derivative where gas (shown as carbon dioxide in Fig. 3) can be adsorbed, i.e., a new gas adsorption mechanism is generated.
[0025] Furthermore, according to the MOF material for shaping of this embodiment and the shaped body composed of such MOF material for shaping, the silane derivative forms a chemical bond with the MOF side functional group to form a siloxane bond (-Si-O-Si-), which is one of the above chemical bonds and has a very large bond energy, thereby increasing the chemical stability of the MOF material for shaping, and as a result, the heat resistance and weather resistance of the MOF material for shaping can be improved. Therefore, even when a relatively high-temperature treatment is performed, such as an activation treatment of MOF in which a temperature exceeding 100°C is applied under vacuum, or when the use conditions are relatively high, it becomes easy to ensure the stability of the MOF material.
[0026] As described above, the MOF material for shaping and the shaped body of this embodiment can increase the gas adsorption amount compared to the MOF constituting the MOF material for shaping. When the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 0 ° C. is measured and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, it is desirable that the MOF material for shaping of this embodiment exhibits a carbon dioxide adsorption amount of 1.5 times or more than that of the MOF having a composition common to the MOF material for shaping of this embodiment except that it does not contain silicon, when the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 25 ....
[0027] Furthermore, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C. and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the shaped object made of the MOF material for shaping of this embodiment desirably exhibits an amount of carbon dioxide adsorption that is 1.5 times or more the amount of carbon dioxide adsorption of an MOF having a composition common to the MOF material for shaping of this embodiment except that it does not contain silicon, when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25 ....
[0028] Here, in the MOF material or shaped body of the present embodiment described above, "MOF having a composition common to the MOF material of the present embodiment except for not containing silicon" can be the MOF used as the target to which the silane derivative is added when preparing the MOF material. In order to identify the MOF corresponding to "MOF having a composition common to the MOF material of the present embodiment except for not containing silicon" for a specific MOF material or shaped body, the crystal structure of the MOF constituting the target MOF material or shaped body is analyzed by X-ray diffraction (XRD) and compared with known information related to the crystal structure, such as the Cambridge Crystal Structure Database (CSD) provided by the Cambridge Crystallographic Data Center (CCDC). In the following, "MOF having a composition common to the MOF material of the present embodiment except for not containing silicon" is also referred to as "raw material MOF". When the starting MOF has MOF-side functional groups introduced, the starting MOF can be identified by combining quantitative analysis techniques such as nuclear magnetic resonance analysis (NMR) and infrared spectroscopy (IR) in addition to the above-mentioned XRD analysis. In order to identify the starting MOF including the introduction state of the MOF-side functional groups, the change in the value of the MOF's BET specific surface area caused by the introduction of the MOF-side functional groups (for example, the BET specific surface area of the previously mentioned UiO-66 is 1500 m) can be determined.2 / g, whereas the BET specific surface area of UiO-66-COOH (Figure 1), which has a carboxyl group introduced, is 700 m 2 / g), the magnitude of the OH vibration peak in IR analysis, or the difference in the amount of thermal decomposition or the oxidative decomposition temperature in simultaneous thermogravimetry and differential thermal analysis (TG-DTA analysis) may also be used.
[0029] Furthermore, when the carbon dioxide adsorption / desorption isotherm of the MOF material for shape transfer of the present embodiment was measured at a measurement temperature of 0° C., the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 45 cm 3 (STP) / g or more. In addition, when the carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C., the carbon dioxide adsorption amount at an absolute pressure of 0.4 is preferably 25 cm 3 (STP) / g or more.
[0030] In addition, the shaped object made of the MOF material for shaping of the present embodiment has a carbon dioxide adsorption amount of 40 cm at an absolute pressure of 0.4 when the carbon dioxide adsorption and desorption isotherm is measured at a measurement temperature of 0°C. 3 (STP) / g or more. In addition, the shaped object made of the MOF material for shaping of the present embodiment has a carbon dioxide adsorption amount of 20 cm at an absolute pressure of 0.4 when a carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C. 3 (STP) / g or more. The carbon dioxide adsorption amount at an absolute pressure of 0.4 when the carbon dioxide adsorption / desorption isotherm of the above-mentioned MOF material for shaping or shaped body is measured refers to the carbon dioxide adsorption amount shown by the lower adsorption curve in the carbon dioxide adsorption / desorption isotherm.
[0031] The properties related to the carbon dioxide adsorption amount in the MOF material for shaping or the shaped body as described above can be appropriately adjusted, for example, by the combination of the complex metal and organic ligand constituting the MOF, and the type of silane derivative added to the MOF, etc. For example, when UiO-66-COOH, which is a Zr-based MOF UiO-66 with a carboxyl group (-COOH) as a MOF side functional group, is used as the MOF, and 1,6-bis(trimethoxysilyl)hexane (e.g., KBM-3066 manufactured by Shin-Etsu Chemical Co., Ltd.) with six methylene groups is used as the silane derivative, it becomes possible to easily satisfy the above-mentioned numerical value related to the carbon dioxide adsorption amount. EXAMPLES
[0032] <Preparation of MOF materials and shaped bodies for use as excipients> FIG. 4 is an explanatory diagram showing the MOF material for shaping and the shaped body prepared for the performance evaluation. Samples S1 to S3 are powdered MOF materials for shaping. Samples S4 to S10 are shaped bodies molded from the MOF materials for shaping. Sample S11 is the MOF (raw material MOF) used as a material for preparing Samples S1 to S10. When preparing Samples S1 to S10, a silane derivative having a functional group capable of forming a chemical bond with the MOF-side functional group of the raw material MOF was added to the raw material MOF to prepare the MOF material for shaping. As the raw material MOF for preparing the MOF material for shaping according to Samples S1 to S10, that is, the MOF of Sample S11, UiO-66-COOH (manufactured by Atomis Corporation) in which a carboxy group (-COOH) was introduced into the UiO-66 described above was used. In addition, the silane derivative added to the raw material MOF was 1,6-bis(trimethoxysilyl)hexane (KBM-3066 manufactured by Shin-Etsu Chemical Co., Ltd.) The preparation of each sample will be described below in order.
[0033] [Samples S1-S3] The MOF material for molding, samples S1 to S3, was prepared by mixing and stirring the MOF (UiO-66-COOH), silane derivative (KBM-3066), and organic solvent (ethanol) at room temperature for 24 hours, removing the solvent by suction filtration, and vacuum drying for 5 hours at 130°C. The amount of silane derivative added when preparing each sample (ratio of silane derivative to the total of MOF and silane derivative) was 2.5wt% for sample S1, 5wt% for sample S2, and 10wt% for sample S3.
[0034] [Samples S4, S9, S10] The MOF material for excipient of sample S2 was compression molded to produce the shaped bodies of samples S4, S9, and S10. Specifically, the MOF material for excipient of sample S2 was uniaxially pressed to form a cylindrical shape with a diameter of 3 mm and a height of 3 mm (corresponding to an average particle size of 3 mm). The pressure (press load) during compression was 1 MPa for samples S4 and S9, and 5 MPa for sample S10. Sample S4 was not tapped, while samples S9 and S10 were tapped. Here, "tapping" refers to the process of filling the MOF material for excipient with a firm filling while tapping (vibrating up and down) for compression molding.
[0035] [Sample S5~S8] The shaped body of sample S5 was produced by extrusion molding the MOF material for excipient of sample S2. The shaped body of samples S6 to S8 was produced by extrusion molding the MOF material for excipient of sample S1. Specifically, the MOF material for excipient of sample S1 or S2 was mixed with polyvinylpyrrolidone (K-85, manufactured by Nippon Shokubai Co., Ltd.) as a binder, and pure water was added and kneaded, and the mixture was then subjected to an extrusion molding machine to form a cylindrical shape with a diameter of 3 mm and a height of 3 mm (corresponding to an average particle size of 3 mm). The amount of binder added (the ratio of the binder to the total of the MOF material for excipient and the binder) was 5 wt% for samples S5 and S6, 10 wt% for sample S7, and 20 wt% for sample S8.
[0036] <Measurement method> (Calculation of Specific Surface Area) The specific surface area of the sample was evaluated using the BET multipoint method. The BET specific surface area is expressed as the area per unit weight, with the unit of " 2 m / g".
[0037] (Calculation of Gas Adsorption Amount) The gas adsorption amount (carbon dioxide adsorption amount) was measured by the volumetric method (in accordance with JIS Z8831-2 and JIS Z8831-3) using a gas adsorption amount measuring device, and the gas adsorption amount was calculated by creating an adsorption / desorption isotherm.
[0038] (Calculation of Atomic Fraction of Complex Metal and Si in MOF) The atomic fraction was determined by performing quantitative mapping (weight %) of elements using a transmission electron microscope equipped with EDS (TEM-EDS).
[0039] (Confirmation of Localization of Si on MOF Particle Surface) Figures 5A and 5B are TEM images when elemental mapping was performed on sample S2, and Figures 6A and 6B are TEM images when elemental mapping was performed on sample S11. Figures 5A and 6A are analysis images of elemental mapping of zirconium (Zr), and Figures 5B and 6B are analysis images of elemental mapping of silicon (Si).
[0040] As shown in Figures 5A and 6A, the results of elemental mapping of Zr confirmed that Zr exists throughout the crystal particles of MOF in both sample S2 corresponding to the MOF material for shaping of the embodiment and sample S11, which is the raw material MOF constituting the MOF material for shaping. In contrast, as shown in Figures 5B and 6B, the results of elemental mapping of Si confirmed that in sample S2, Si exists locally on the surface of the crystal particles of MOF, and in sample S11, a signal thought to be background exists in the area where no crystal particles exist on the entire screen, and the presence of Si was not recognized. Note that Figures 5A and 5B show the results of sample S2, but in samples S1, S3 to S10 corresponding to the MOF material for shaping of the embodiment and the shaped body, the presence of Si is similarly recognized to be localized on the surface of the crystal particles of MOF (data not shown).
[0041] <Atomic fraction> FIG. 7 is an explanatory diagram showing the results of calculating the atomic fractions of samples S1 to S3 and sample S11. FIG. 8 is an explanatory diagram showing a graph in which the calculation results of the atomic fractions shown in FIG. 7 are plotted. As described above, samples S1 to S3 differ in the amount of silane derivative added to the raw material MOF when each sample was produced. In FIG. 8, the horizontal axis shows the amount of silane derivative added, and the vertical axis shows the atomic fraction of Si. FIG. 7 and FIG. 8 show the results of measuring the atomic fraction twice for each sample.
[0042] As shown in FIG. 8, up to about 0.5 wt% of the silane derivative, there was a positive correlation between the amount of the silane derivative and the Si atomic fraction, and the Si atomic fraction increased as the amount of the silane derivative increased. However, even if the amount of the silane derivative was increased beyond 0.5 wt%, the increase in the Si atomic fraction was suppressed. This is thought to be because the excess silane derivative that was not used to bond with the MOF-side functional group on the MOF surface was removed together with the solvent when the solvent was removed from the MOF in the manufacturing process of the MOF material for shaping. In addition, from the results shown in FIG. 8, it can be understood that if the Si atomic fraction is 0.02 or more, it can be said that there is an amount of Si that can be sufficiently distinguished from the background in the MOF material for shaping. In the MOF material for shaping, by setting the amount of the silane derivative to 2.5 wt% or more, it is possible to easily achieve a Si atomic fraction of 0.02 or more, and as a result, it is thought that the effect of facilitating shaping by localizing Si on the surface of the crystal particles constituting the MOF can be more fully obtained.
[0043] <Amount of carbon dioxide adsorbed> FIG. 9 is an explanatory diagram showing the results of measuring the carbon dioxide adsorption / desorption isotherms for samples S1 to S3 and S11 at a measurement temperature of 25° C. In FIG. 9, the horizontal axis indicates absolute pressure, and the vertical axis indicates the amount of adsorbed carbon dioxide. As shown in FIG. 9, all of the carbon dioxide adsorption / desorption isotherms for samples S1 to S3 are shifted upward from the carbon dioxide adsorption / desorption isotherm for sample S11, and it was confirmed that the amount of adsorbed carbon dioxide increased by adding the silane derivative to the MOF. It was also confirmed that, within the range of the amount of added silane derivative of 2.5 wt % to 10 wt %, the smaller the amount of added silane derivative, the greater the degree of increase in the amount of adsorbed carbon dioxide. Specifically, for example, by setting the amount of added silane derivative to 5 wt % or less, the amount of adsorbed carbon dioxide at an absolute pressure of 0.4 when measuring the carbon dioxide adsorption / desorption isotherm at a measurement temperature of 25° C. was increased by 25 cm 3 (STP) / g or more.
[0044] FIG. 10 is an explanatory diagram showing the results of measuring the BET specific surface area and the carbon dioxide adsorption amount at 0° C. for samples S2, S4, S5, and S11. FIG. 11 is an explanatory diagram showing the results of measuring the carbon dioxide adsorption / desorption isotherm at a measurement temperature of 0° C. for samples S2, S4, S5, and S11. FIG. 12 is an explanatory diagram showing the results of measuring the BET specific surface area and the carbon dioxide adsorption amount at 25° C. for samples S2, S4, S5, and S11. FIG. 13 is an explanatory diagram showing the results of measuring the carbon dioxide adsorption / desorption isotherm at a measurement temperature of 25° C. for samples S2, S4, S5, and S11.
[0045] 10 and 12 show the results of measuring the BET specific surface area twice for sample S5 and sample S11. In addition, in FIG. 10 and FIG. 12, the maximum carbon dioxide adsorption amount is shown as the carbon dioxide adsorption amount, that is, the adsorption amount at an absolute pressure of 1.00 in the carbon dioxide adsorption and desorption isotherms shown in FIG. 11 and FIG. 13. In addition, in FIG. 10 and FIG. 12, for samples S2, S4, and S5, the increase ratio compared to the carbon dioxide adsorption amount of sample S11 is shown in parentheses along with the carbon dioxide adsorption amount. In the following, the ratio of the carbon dioxide adsorption amount of the MOF material for shaping or the shaped body to the carbon dioxide adsorption amount of the MOF (raw material MOF) having a composition common to the MOF material for shaping except that it does not contain silicon at a specific measurement temperature and absolute pressure is also referred to as the "increase ratio".
[0046] As shown in Figures 9 to 13, it was confirmed that samples S1 to S3, which are MOF materials for shaping in which a silane derivative is added to MOF, sample S4 obtained by compression molding sample S2, and sample S5 obtained by extrusion molding sample S2, have a significantly increased amount of carbon dioxide adsorption compared to the MOF before the addition of the silane derivative at both measurement temperatures of 0 ° C. and 25 ° C. As shown in Figure 10, under the conditions of an absolute pressure of 1.00 at which the amount of carbon dioxide adsorption is maximized and a measurement temperature of 0 ° C., the increase ratio of the amount of carbon dioxide adsorption compared to sample S11 was 2.3 times for sample S2, 2.15 times for sample S4, and 2.4 times for sample S5. In addition, as shown in Figure 12, under the conditions of an absolute pressure of 1.00 at which the amount of carbon dioxide adsorption is maximized and a measurement temperature of 25 ° C., the increase ratio of the amount of carbon dioxide adsorption compared to sample S11 was 3.1 times for sample S2, 2.65 times for sample S4, and 3.1 times for sample S5.
[0047] When the carbon dioxide adsorption / desorption isotherm at a measurement temperature of 0° C. is measured and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the MOF material for shaping as described above can exhibit a carbon dioxide adsorption amount 1.5 times or more of the carbon dioxide adsorption amount of the MOF (raw material MOF) having a common composition with the MOF material for shaping as described above except that it does not contain silicon. In addition, when the carbon dioxide adsorption / desorption isotherm at a measurement temperature of 25° C. is measured and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, it was confirmed that the MOF material for shaping as described above (for example, samples S1 to S3 shown in FIG. 9) can exhibit a carbon dioxide adsorption amount 1.5 times or more of the carbon dioxide adsorption amount of the raw material MOF (for example, sample S110 shown in FIG. 9).
[0048] In addition, when the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 0 ° C. is measured for the shaped body (for example, samples S4 and S5 shown in FIG. 11) molded from the MOF material for molding, and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, it is confirmed that the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of the MOF (raw material MOF, for example, sample S11 shown in FIG. 11) having a common composition with the MOF material for molding except that it does not contain silicon, can be shown. In addition, when the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 25 ° C. is measured for the shaped body (for example, samples S4 and S5 shown in FIG. 13) molded from the MOF material for molding is measured, and the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, it is confirmed that the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of the raw material MOF (for example, sample S11 shown in FIG. 13).
[0049] As shown in the above-mentioned Figures 9, 11, and 13, and Figures 14 and 15 described later, the carbon dioxide adsorption and desorption isotherms of the MOF (sample S11), the MOF material for shaping in which a silane derivative is added to the MOF (samples S1 to S3), and the shaped body molded from the MOF material for shaping (samples S4 to S10) are so-called type I adsorption and desorption isotherms, which are generally seen in the adsorption and desorption isotherms of adsorbents and the like having micropores with a pore diameter of 2 nm or less. Therefore, when the absolute pressure is relatively low (for example, an absolute pressure less than 0.3), the amount of carbon dioxide adsorption increases rapidly with an increase in the absolute pressure, and when the absolute pressure is relatively high (for example, an absolute pressure of 0.3 or more), the degree of increase in the amount of carbon dioxide adsorption with an increase in the absolute pressure is suppressed. Moreover, not only when the absolute pressure is relatively low, but also when the absolute pressure is relatively high, the slope of the carbon dioxide adsorption / desorption isotherm of the MOF material for shaping (samples S1 to S3) and the shaped body (samples S4 to S10) in which a silane derivative is added to MOF is larger than the slope of the carbon dioxide adsorption / desorption isotherm of the MOF (raw MOF, sample S11) having a common composition with the above-mentioned MOF material for shaping except that it does not contain silicon, regardless of the measurement temperature. Therefore, when the carbon dioxide adsorption amount of the MOF material for shaping or the shaped body at an absolute pressure of 0.4 shows a specific value relative to the carbon dioxide adsorption amount of the raw MOF at an absolute pressure of 0.4, it can be said that the increase ratio shows the specific value or more under the condition of an absolute pressure of 0.4 or more.
[0050] In the MOF material for molding described above, the amount of carbon dioxide adsorption at an absolute pressure of 0.4 in the carbon dioxide adsorption / desorption isotherm measured at 0°C was 45 cm 3 (STP) / g or more. In addition, in the carbon dioxide adsorption / desorption isotherm measured at 25°C, the carbon dioxide adsorption amount at an absolute pressure of 0.4 is 25 cm 3 (STP) / g) or more (for example, samples S1 and S2 shown in FIG. 9).
[0051] In addition, in the case of a molded MOF material, the amount of carbon dioxide adsorption at an absolute pressure of 0.4 measured at 0°C was 40 cm3 (STP) / g) or more (for example, samples S4 and S5 shown in FIG. 11). In addition, in the case of a shaped body molded from the MOF material for shaping, the carbon dioxide adsorption amount at an absolute pressure of 0.4 in the carbon dioxide adsorption / desorption isotherm measured at 25°C was 20 cm 3 (STP) / g or more (for example, samples S4 and S5 shown in FIG. 13, samples S6 to S8 shown in FIG. 14, and samples S4 and S9 shown in FIG. 15).
[0052] <Extrusion molding conditions> FIG. 14 is an explanatory diagram showing the results of measuring the carbon dioxide adsorption / desorption isotherms at a measurement temperature of 25° C. for sample S1, which is a MOF material for shaping, and S6 to S8, which are shaped bodies obtained by extrusion molding of the MOF material for shaping. It was confirmed that the amount of carbon dioxide adsorption increased in all of samples S1 and S6 to S8 compared to the raw MOF (see, for example, sample S11 in FIG. 9 and FIG. 13). Samples S6 to S8, which are extrusion molded bodies, were molded by adding a binder (PVP), and it was confirmed that the amount of carbon dioxide adsorption was suppressed as the amount of binder added increased, as shown in FIG. 14. However, sample S6, which had the smallest amount of binder added (5 wt%), showed the same amount of carbon dioxide adsorption as sample S1, which is a MOF material for shaping that does not contain a binder. This is thought to be because, as explained with reference to FIG. 3, a new site where gas can be adsorbed between the surface of MOF and the silane derivative was formed by adding a silane derivative to MOF and bonding the MOF and the silane derivative. In other words, it is believed that the occurrence of a new gas adsorption mechanism cancelled out the effect of adding a small amount of binder, resulting in almost no change in the amount of carbon dioxide adsorption. Furthermore, since the pressure applied during extrusion molding is smaller than that applied during compression molding, and the degree to which the MOF particles are pressed down is relatively small, it is believed that gas can easily circulate to the inside of the shaped body, making it easier to ensure the amount of carbon dioxide adsorption.
[0053] <Compression molding conditions> FIG. 15 is an explanatory diagram showing the results of measuring the carbon dioxide adsorption / desorption isotherms at a measurement temperature of 25° C. for S4, S9, and S10, which are shaped bodies obtained by compression molding the MOF material for molding. It was confirmed that the amount of carbon dioxide adsorption was increased in all of samples S4, S9, and S10 compared to the raw MOF (see, for example, sample S11 in FIG. 9 and FIG. 13). As shown in FIG. 15, the amount of carbon dioxide adsorption in the shaped body was reduced the greater the press load during compression molding (samples S9 and S10). In addition, the amount of carbon dioxide adsorption in the shaped body was reduced by providing a tap (filling while tapping during compression molding) (samples S4 and S9).
[0054] The present disclosure is not limited to the above-mentioned embodiments, etc., and can be realized in various configurations without departing from the spirit of the present disclosure. For example, the technical features in the embodiments corresponding to the technical features in each form described in the Summary of the Invention column can be appropriately replaced or combined in order to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if a technical feature is not described as essential in this specification, it can be appropriately deleted.
[0055] The present disclosure can also be realized in the following forms. [Application example 1] A metal-organic framework (MOF) material for shaping, The MOF is characterized in that it contains silicon (Si) localized on the surface of the crystal particles constituting the MOF. MOF material for shaping. [Application example 2] The MOF material for shaping according to Application Example 1, The atomic fraction ratio of the complex metal contained in the MOF to silicon (Si) (complex metal contained in the MOF:Si) is 0.98:0.02 to 0.9:0.10. MOF material for shaping. [Application example 3] A shaped object, characterized by being composed of the MOF material for shaping described in Application Example 1 or 2. [Application example 4] The shaped object according to Application Example 3, Characterized by an average particle size of 1 mm or more Forming body. [Application example 5] The MOF material for shaping according to Application Example 1 or 2, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. MOF material for shaping. [Application Example 6] The MOF material for shaping according to any one of Application Examples 1, 2, and 5, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. MOF material for shaping. [Application Example 7] The shaped body according to Application Example 3 or 4, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. Forming body. [Application Example 8] The shaped body according to any one of Application Examples 3, 4, and 7, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. Forming body. [Application Example 9] The MOF material for shaping according to any one of Application Examples 1, 2, 5, and 6, When measuring the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 0°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 45 cm 3 (STP) / g or more MOF material for shaping. [Example 10] The MOF material for shaping according to any one of Application Examples 1, 2, 5, 6, and 9, When measuring the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 25°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 is 25 cm 3 (STP) / g or more MOF material for shaping. [Application Example 11] The shaped body according to any one of Application Examples 3, 4, 7, and 8, When measuring the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 0°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 is 40 cm 3 (STP) / g or more Forming body. [Application Example 12] The shaped body according to any one of Application Examples 3, 4, 7, 8, and 11, When measuring the carbon dioxide adsorption and desorption isotherm at a measurement temperature of 25°C, the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 20 cm 3 (STP) / g or more Forming body. [Application Example 13] A gas adsorbent for adsorbing and releasing gas, comprising: The present invention is characterized in that the shaped body is constituted by the shaped body according to any one of Application Examples 3, 4, 7, 8, 11, and 12. Gas adsorbent. [Example 14] A gas adsorption device comprising the gas adsorbent according to Application Example 13. [Example 15] A method for producing a MOF material for molding, comprising the steps of: A silane derivative having a functional group capable of forming a chemical bond with the functional group on the surface of the MOF is added to the metal-organic framework (MOF). A method for producing MOF materials for shaping.
Claims
1. A metal-organic framework (MOF) material for shaping, The MOF is characterized in that it contains silicon (Si) localized on the surface of the crystal particles constituting the MOF. MOF material for shaping.
2. The MOF material for shaping according to claim 1, The ratio of the atomic fraction of the complex metal contained in the MOF to that of silicon (Si) (complex metal contained in the MOF:Si) is 0.98:0.02 to 0.9:0.
10. MOF material for shaping.
3. A shaped body, comprising the MOF material for shaping according to claim 1.
4. The shaped body according to claim 3, The average particle size is 1 mm or more. Forming body.
5. The MOF material for shaping according to claim 1 or 2, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. MOF material for shaping.
6. The MOF material for shaping according to claim 1 or 2, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. MOF material for shaping.
7. The shaped body according to claim 3, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 0° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. Forming body.
8. The shaped body according to claim 3, The carbon dioxide adsorption / desorption isotherm is measured at a measurement temperature of 25° C., and when the carbon dioxide adsorption amount at an absolute pressure of 0.4 or more is compared, the carbon dioxide adsorption amount is 1.5 times or more the carbon dioxide adsorption amount of an MOF having a common composition with the MOF material for shaping except that it does not contain silicon. Forming body.
9. The MOF material for shaping according to claim 1 or 2, When the carbon dioxide adsorption / desorption isotherm was measured at a measurement temperature of 0° C., the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 45 cm 3 (STP) / g or more MOF material for shaping.
10. The MOF material for shaping according to claim 1 or 2, When the carbon dioxide adsorption / desorption isotherm was measured at a measurement temperature of 25° C., the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 25 cm 3 (STP) / g or more MOF material for shaping.
11. The shaped body according to claim 3, When the carbon dioxide adsorption / desorption isotherm was measured at a measurement temperature of 0° C., the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 40 cm 3 (STP) / g or more Forming body.
12. The shaped body according to claim 3, When the carbon dioxide adsorption / desorption isotherm was measured at a measurement temperature of 25° C., the amount of carbon dioxide adsorbed at an absolute pressure of 0.4 was 20 cm 3 (STP) / g or more Forming body.
13. A gas adsorbent for adsorbing and releasing gas, comprising: A shaped body according to any one of claims 3, 4, 7, 8, 11 and 12. Gas adsorbent.
14. A gas adsorption device comprising the gas adsorbent according to claim 13.
15. A method for producing an MOF material for molding, comprising the steps of: A silane derivative having a functional group capable of forming a chemical bond with the functional group on the surface of the MOF is added to the metal-organic framework (MOF). A method for producing MOF materials for use as excipients.
Citation Information
Patent Citations
Preparing method, product and application of core-shell-structure-silicon-dioxide-coated-cobaltosic-oxide catalyst for propane governance
CN110064399A
Metal organic framework complex composite wave-absorbing powder and preparation method thereof
CN113249092A
Metal-organic framework materials for gaseous hydrocarbon storage
JP2008531939A
JP1974080918A
Amino acid derivative and hypotensor containing said derivative
JP1987072696A